The dispersal of a dry-fruited shrub by red deer in a Mediterranean ecosystem - Malo, Juan E.; Suárez, Francisco (Ecography, 1998)
Seed dispersal of dry-fruited shrubs has received little attention in Mediterranean areas despite their frequency in the vegetation and the consideration given to the dispersal of fleshy-fruited shrubs in the area. Red deer faeces has recently been found to contain large numbers of seeds from one of the most common shrubs of this group, gum cistus Cistus ladanifer, although its importance in the reproduction of the species is unknown. This study examines the role of the red deer as an effective disperser of C. ladanifer. For this purpose, we quantify i) the C. ladanifer seed content in red deer dung over a year, ii) the seed shadow generated by the red deer wish their faeces during the same period, and iii) the ability of the dung-borne seeds to germinate and establish as seedlings under field conditions within five years following excretion. The results reveal an extremely high seed Content of the species in red deer dung (up to 80.5 ± 41.9 germinable seeds g-1), which is virtually confined to the summer (July–August), when we estimate that a red deer defecates up to 24 000 seeds of the species per day. Furthermore, red deer mainly deposit gum cistus seeds amongst plant formations lacking the species: over the year, red deer excrete <2600 seeds m-2 in C. ladanifer-dominated scrub and 7400–8800 seeds m-2 in other plant formations. Under natural conditions, the dung-borne seeds have a more sniggered among-years germination pattern than free seeds in the soil. Though no seedling survived its first summer drought, the survival of seedlings sprouted from dung was significantly longer than that of control seedlings in the first and third years after deposition, and indistinguishable from it the second, fourth and fifth years. This is the first quantification of the importance of red deer to C. ladanifer dispersal and establishment, and suggests that endozoochory by mammalian herbivores can be very valuable for dry-fruited shrubs in the Mediterranean region.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: endozoochory; red deer; seed dispersal; seedling establishment (PG)